Dalla guerra alla pace. L'Arazzo di Bayeux e la conquista normanna dell'Inghilterra (secolo XI) - PROVERO, Luigi (Reti Medievali E-Book, 2020)
The Bayeux Tapestry (or rather, embroidery) is one of the most famous medieval artworks, which narrates in images the conquest of England by the Normans led by Duke William the Conqueror. Images taken from the embroidery are reproduced on thousands of objects evoking the Middle Ages, and at the same time the work has been the subject of hundreds of studies in many European countries, by historians, art historians and narrative scholars. In all of this, some questions and some answers are lacking, in particular with regard to the political culture expressed in the work: there is no doubt that the embroidery is a narrative of the exploits of William the Conqueror, an attempt to reconcile the English and Normans and in part an exaltation of the role of Odo, bishop of Bayeux; but it is also the expression of a series of political ideals and models of order, a reading and an evaluation of the system of contemporary power, organized around the kingdom and based on the primacy of the aristocracy and the value of personal ties. The volume aims to follow this line of research, showing how the embroidery, from many points of view (the political ceremonial, the role of the king, the aristocratic bonds of fidelity), reflects a social imaginary and a series of clearly recognizable political ideals.